Financial frictions in a housing economy: Multiple credit constraints, internal migration, and bank runs - Marcus Mølbak Ingholt (University of Copenhagen, Department of Economics, 2019)
More than a decade has now passed since rapidly declining house prices triggered a global financial crisis that developed into a global recession, the speed and depth of which were unprecedented in recent history. The overarching objective of this Ph.D. thesis is to improve our understanding of how simple price adjustments in the housing market could cause havoc to the functioning of the global economy to such an extent. At first sight, it may not be obvious that housing markets matter greatly for aggregate economic activity. For instance, residential investments constitute a small share - 4.4 pct. in the United States (U.S.) and 5.4 pct. in Denmark - of the gross domestic product.1 However, real estate, in addition to providing housing services to families, serves as collateral on mortgage loans, home equity loans, and home equity lines of credit. A corollary of this servitude is that the supply of collateralized credit to homeowners expands and contracts roughly proportionally to the house price cycle. In consequence, house prices may act as impetuses that stimulate and depress economic activity (Kiyotaki and Moore, 1997; Iacoviello, 2005). This collateral channel - in conjunction with other mechanisms linking house prices, credit, and real activity - constitute the theoretical foundation of the thesis. The thesis consists of three self-contained chapters, in addition to this introduction. All chapters focus on the U.S. economy, but have implications that reach well beyond this scope.
Keywords: 330